Diagnostic tools for balanced and integrated nutrient management in food crops - Jha, A.K.; Singh, K.K. (Annals of Agricultural Research, 2014)
India has to ensure food security of more than 18% world’s population in about 2.5% of world’s area. Due to geometrical multiplication of India’s population, this task has become more difficult. India is bound to produce at least 325 Mt food grain by 2025 without much increase in irrigated crop land. To achieve this target, it is needed to revamp the supply system of quality inputs in every part of the country and to assure their scientific and judicious management to fetch the maximum benefits. As fertility of the soil decides thefertilizer recommendation for a particular crop, so this is very high time to ascertain soil fertility. There are so many ways to determine fertility of the soils, but some important diagnostic tools used for fertilizermanagement have been discussed in this paper to obtain the maximum benefit of fertilizer use in agriculture.